Assessing the Impact of Religious Extremism on Educational Progress in Nigeria through a Comparative Study of Geopolitical Zones in the North, East, and West (International Journal of Scientific Research in Science and Technology, 2024)
Religious extremism poses significant challenges to educational progress in Nigeria, particularly across the diverse geopolitical zones of the North, East, and West. This study examines the impact of religious extremism on educational systems within these regions, highlighting variations in access, quality, and outcomes of education. Through a comparative analysis, the paper explores how sociopolitical and cultural factors shape the intersection of religion and education, exacerbating inequalities in educational attainment. Utilizing a mixed-methods approach, the study incorporates primary data from stakeholder interviews and secondary data from governmental and institutional reports to identify trends and regional disparities. The findings reveal that while the North grapples with the highest disruptions due to insurgency and religious conflicts, the East and West face subtler but impactful religious dynamics that influence educational priorities. This paper underscores the urgent need for tailored policy interventions to mitigate the influence of extremism on education and foster resilience within affected communities. It advocates for collaborative efforts among government, religious leaders, and educational stakeholders to address root causes, enhance educational access, and promote inclusive learning environments. By addressing the intersection of religion and education, this research provides actionable insights to strengthen Nigeria’s educational framework and contribute to sustainable national development.